Effect of three diets on the gametogenic development and fatty acid profile of Paracentrotus lividus (Lamarck, 1816) gonads. (10th May 2019) - Raposo, Andreia I. G.; Ferreira, Susana M. F.; Ramos, Rodolfo; Santos, Pedro M.; Anjos, Catarina; Baptista, Teresa; Tecelão, Carla; Costa, José L.; Pombo, Ana
Abstract: In this study, the effects of three diets were investigated to enhance Paracentrotus lividus production for commercial purposes. P. lividus were fed ad libitum for 80 days with: diet A—fresh Codium tomentosum Stackhouse, 1797; diet B—formulated using a jellified mix of macroalgae and vegetables, including C. tomentosum (20%), Coralina sp. Linnaeus, 1758 (17%), cabbage Brassica oleracea var. capitata Linnaeus, 1753 (30%), carrot Daucus carota Linnaeus, 1753 (30%) and agar (3%) as a gelling agent. Diet C consisted of maize Zea mays Linnaeus, 1753 (56%) and New Zealand spinach Tetragonia tetragonoides (Pallas, 1781) Kuntze, 1891 (44%). Their effects on the gonadal and somatic growths, gonadosomatic index (GI) and gametogenesis were evaluated, as well as on the total lipid content and fatty acid composition of sea urchin's gonads. Diet A provided high values of eicosapentaenoic acid (EPA). Gonads of sea urchins fed with diet A were found mostly in growth and maturation stages of gametogenesis and showed the lowest lipid content. Sea urchins fed with diet B presented their gonads in the reabsorption stage and had the highest values of omega‐3 polyunsaturated fatty acids (PUFAs). Sea urchins fed with diet C were in the early stages of gametogenesis and had the highest values of lipid content, plus omega‐6 PUFAs. Once as an ingredient in a balanced mix with vegetables, C. tomentosum can be a key factor to the development of new promising high‐quality and low‐cost feed for P. lividus roe enhancement.